Luteinizing hormone-releasing hormone agonists for prostate cancer patients: routine clinical practice of Russian cancer urologists - V. B. Matveev (Onkourologiâ, 2021)
Background. Despite the recent amendments to the guidelines for the treatment of metastatic hormone-sensitive prostate cancer (PCa) implying standard use of luteinizing hormone-releasing hormone (LHRH) agonists in combination with chemotherapy or androgen inhibitors, androgen deprivation therapy (ADT) remains an essential component of treatment for advanced PCa. Testosterone target castration level of 20 ng/dL implies routine measurement of testosterone levels along with prostate-specific antigen (PSA) levels during ADT. It is particularly interesting to evaluate the frequency of achieving castration testosterone level in routine clinical practice. Objective: to assess the frequency of achieving castration testosterone level (20 ng/dL) and maintaining it after 6 months of therapy in patients with hormone-sensitive PCa receiving an LHRH agonist for the first time. Materials and methods. In 2019-2020, Russian Society of Cancer Urologists conducted a non-interventional prospective multicenter study (observational program) aimed to evaluate the efficacy of LHRH agonist (including buserelin, goserelin, leuprorelin or triptorelin) in routine clinical practice in Russia. This study involved 39 cancer urologists and 479 patients aged 18 years and older diagnosed with hormone-sensitive PCa, who started their ADT with LHRH agonists for the first time regardless of the disease stage and previous treatment. Patients received hormone therapy with an LHRH agonist for at least 6 months, visiting their doctor every 3 months (visit 1; visit 2: after 3 months; visit 3: after 6 months). Results. Patients received one of the following drugs: leuprorelin (3.75 mg; 7.5 mg; 22.5 mg; 45 mg; n = 225; 47,0 %), goserelin (3.6 mg; 10.8 mg; n = 132; 27.5 %), buserelin (3.75 mg; n = 67; 14.0 %), and triptorelin (3.75 mg; 11.25 mg; n = 55; 11.5 %). Of 479 patients, 186 (38.8 %) received combination treatment with bicalutamide, 12 (2.5 %) with fluta-mide, 54 (11.3 %) with zoledronic acid, and 11 (2.3 %) with denosumab. Among 146 patients with metastatic PCa, a combination of ADT plus docetaxel was administered to 30 participants (20.6 %), ADT plus abiraterone to 8 participants (5.5 %), and ADT plus enzalutamide to 2 participants (1.4 %). After 6 months of therapy, mean PSA level decreased by 94.2 % (from baseline 118.12 ng/mL to 6.87 ng/mL). Mean testosterone level was 19.0 ng/dL (range: 0.029-100 ng/dL). Among 430 patients, the targeted testosterone level <20 ng/dL was achieved in 257 individuals (59.8 %); the level of 20-50 ng/dL was achieved in 158 individuals (36.7 %); and fifteen patients (3.5 %) had their testosterone level >50 ng/dL. The incidence of adverse events was low; most of them were mild. Conclusion. Our findings suggest that not all patients achieve targeted testosterone level of <20 ng/dL, which corroborates the need for routine monitoring of testosterone levels during therapy to ensure its timely correction. We observed frequent administration of ADT with maximum androgen blockade. In patients with metastatic PCa, the use of standards for combination treatment with docetaxel and androgen inhibitors is limited.